Impact of Student Activity and Environmental Support on Academic Performance at Surakarta High School - Ambawani, Cettra Shandilia Latunusa; Kusuma, Thitha Meista Mulya; Cholidah, Nur; Harsono, Harsono; Masduki, Masduki; Suyatmi, Suyatmi (Bulletin of Science Education, 2024)
This research to find out how student activity and environmental support at Surakarta High School affects their academic achievement in the Sociology subjects will provide valuable insights for educators, parents, and educational stakeholders. Thus, the study aims to systematically analyze the relationship between student activity, environmental support, and academic achievement in the context of learning Sociology at Surakarta High School. This method of research is quantitative using the survey method using google form. Population is a whole student class X Phase E, XI Phase F 6-11 and XII IPS with a sample of 177 students, regression analysis with normality tests, rehabilitation, and hypothesis tests. Thus, the results of this study can be explained by the variables of student activity and environmental support of only 3.1% while the remaining 96.9% are influenced by other factors that are not included in this variable, expected to provide conceptual and practical contributions to improving the quality of learning and student performance at the middle level. Keywords: Academic Performance, Environmental Support, Student Activities